2021
DOI: 10.3389/fmolb.2021.666026
|View full text |Cite
|
Sign up to set email alerts
|

Co-Transmission of Alpha-Synuclein and TPPP/p25 Inhibits Their Proteolytic Degradation in Human Cell Models

Abstract: The pathological association of alpha-synuclein (SYN) and Tubulin Polymerization Promoting Protein (TPPP/p25) is a key factor in the etiology of synucleinopathies. In normal brains, the intrinsically disordered SYN and TPPP/p25 are not found together but exist separately in neurons and oligodendrocytes, respectively; in pathological states, however, they are found in both cell types due to their cell-to-cell transmission. The autophagy degradation of the accumulated/assembled SYN has been considered as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
(131 reference statements)
2
10
0
Order By: Relevance
“…TPPP/p25 and SYN are co-enriched and co-localized in the inclusion bodies of the post-mortem brain tissue of patients with parkinsonism due to their cell-to-cell transmission [ 11 , 38 ]. Recently, we have revealed that the excess SYN and TPPP/p25 can be degraded by autophagy and/or ubiquitin–proteasome system, and their eliminations are inhibited in the presence of specific inhibitors, such as chloroquine and MG132, respectively, indicating their intracellular degradation [ 34 ]. In addition, we have reported that the hetero-association of the two hallmark proteins counteract their degradation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…TPPP/p25 and SYN are co-enriched and co-localized in the inclusion bodies of the post-mortem brain tissue of patients with parkinsonism due to their cell-to-cell transmission [ 11 , 38 ]. Recently, we have revealed that the excess SYN and TPPP/p25 can be degraded by autophagy and/or ubiquitin–proteasome system, and their eliminations are inhibited in the presence of specific inhibitors, such as chloroquine and MG132, respectively, indicating their intracellular degradation [ 34 ]. In addition, we have reported that the hetero-association of the two hallmark proteins counteract their degradation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this set of experiments, the effect of DJ-1 on the degradation of the excess SYN complexed with TPPP/p25 was detected and quantified. SYN and/or TPPP/p25 were taken up from the medium by human cells to mimic the pathological circumstances (cell-to-cell transmission) [ 34 ]. Now, both HeLa and SH-SY5Y cells were used as cell models to monitor the anti-aggregative effect of DJ-1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations